Louise Bennett-Coverley : recipient of 1972 Norman Manley Award - Miss Lou, (Louise Simone Bennett-Coverley), 1919 - 2006; Bennett- Coverley, Louise, (Louise Simone Bennett-Coverley), 1919 - 2006; Graham, Douglas; Nettleford, Rex, (Ralston Milton Nettleford), 1933 - 2010; Manley, Edna, (Edna Swithenbank Manley), 1900 - 1987 (Kingston, Jamaica : Jamaica Information Service (J.I.S.), 1972)
"Good News documenting of Miss Lou receiving the NW Manley Award" -- taken from film transcript. Biographical information on Louise Bennett (N.W. Manley Awardee). Her recollections of events.
Title taken from film transcript.
Douglas Graham, Rex Nettleford, Edna Manley, Louise Bennett-Coverley
1972
Also available as VHS tape and digital video file.
Videocassette.
Electronic reproduction.
Keywords: Manley, Norman, -- 1893 - 1969; Bennett-Coverley, Louise, -- 1919 - 2006; Miss Lou, -- 1919 - 2006